2017
DOI: 10.3389/fpsyg.2016.02049
|View full text |Cite
|
Sign up to set email alerts
|

Infant Massage and Quality of Early Mother–Infant Interactions: Are There Associations with Maternal Psychological Wellbeing, Marital Quality, and Social Support?

Abstract: Infant massage programs have proved to be effective in enhancing post-natal development of highly risk infants, such as preterm newborns and drug or HIV exposed children. Less studies have focused on the role of infant massage in supporting the co-construction of early adult-child relationships. In line with this lack of literature, the present paper reports on a pilot study aimed at investigating longitudinally the quality of mother-child interactions, with specific reference to emotional availability (EA), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…A mixed-method study with several aims and measures found infant massage to improve mother-child interaction (Porreca, Parolin, Bozza, Freato, & Simonelli, 2016). However, few studies describe how mothers experience baby massage, and several research articles have concluded that these questions should be explored further (Bennett et al, 2013;Garmy, 2012;Kristensen et al, 2015).…”
Section: Infant Massagementioning
confidence: 99%
“…A mixed-method study with several aims and measures found infant massage to improve mother-child interaction (Porreca, Parolin, Bozza, Freato, & Simonelli, 2016). However, few studies describe how mothers experience baby massage, and several research articles have concluded that these questions should be explored further (Bennett et al, 2013;Garmy, 2012;Kristensen et al, 2015).…”
Section: Infant Massagementioning
confidence: 99%
“…In addition, an emotionally intense "guided" approach to babies can reassure mothers, who often perceive newborns as fragile and afraid to touch them, making them more confident when holding their babies. From this perspective, infant massage is a valuable resource in terms of primary prevention, that is, in terms of interventions aimed at maintaining and enhancing existing resources in the family system, as it can be offered as enriching support also in the absence of adult psychopathology [32]. Parents all over the world have been massaging their babies for centuries.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the benefits of mother-delivered massage therapy include improved mother-infant interactions and better sleep in the mothers and infants. For example, in a study on infant massage classes, mother-infant interactions were observed and were coded for emotional availability of both the mother and their 2-7-month-old infants (Porreca, Parolin, Bozza, Freato & Simonelli, 2017). Emotinal availability increased for both the mothers and their infants which contributed to their improved motherinfant interactions.…”
Section: Sleepmentioning
confidence: 99%